Protective effect of acrocarpus fraxinifolius extract against hepatic fibrosis induced by Gamma irradiation and carbon tetrachloride in albino rats. (1st February 2023) - El-Shawi, Omama E.; El-Nashar, Heba A. S.; Abd El-Rahman, Sahar S.; Eldahshan, Omayma A.; Singab, Abdel Nasser B.
Abstract: Purpose: Liver fibrosis is considered as one of the ultimate outcomes of chronic liver disorders, characterized by outrageous cell proliferation and abnormal deposition of extracellular matrix, resulting in sever pathological distortions in the architecture and performance of liver tissues. The present study aimed to investigate the protective properties of aqueous methanol extract of Acrocarpus fraxinifolius leaves (AFL) against liver fibrosis induced by dual toxicity of γ-irradiation and carbon tetrachloride (CCl4 ) in rats. Methods: The animals were exposed to 2 Gy irradiation once/week concurrently with intraperitoneal administration of CCl4 (0.2 mL/100 g body weight) for seven weeks. Afterwards, liver toxicity and fibrosis were assessed biochemically at cellular and molecular as well as histopathological levels. Results: The livers of intoxicated rats showed distinct structural and functional changes, compared with the normal rats. The administration of AFL (500 mg/kg, p.o ) significantly ameliorated the histopathological manifestations of fibrotic liver evidenced by mitigated steatosis progression, necrosis, fibrotic septa, apoptotic bodies, and immunochistochemical studies of alpha-smooth muscle actin. Also, AFL increased the final body weight, total protein, albumin levels and albumin/globulin ratio. While, the absolute liver weight, liver enzymes, total cholesterol and triglycerides were reduced. A significant modulation was observed in hydroxyproline, transforming growth factor- β and collagen-1expression. Furthermore, AFL exerted a direct effect on liver fibrosis by promoting extracellular matrix degradation via overexpression of the tissue inhibitor metalloproteinase-1, coupled with decease of metalloproteinase-9 activity. Conclusions: Our findings suggested that AFL effectively improved the architecture of fibrotic liver and modified the biochemical markers of liver fibrosis. Graphical Abstract: UF0001